Khaá¹£Äâ€™iá¹£ MuÊ»jam al-Lughah al-Ê»Arabiyyah fÄ« al-MaÊ»had al-IslÄmiy: DirÄsah Lughawiyyah AnthirÅ«bÅ«lÅ«jiyyah - Solichah, Badi'atus; Suhandano, Suhandano (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2023)
This research aims to find and describe the characteristics of Arabic lexicon variations in the Islamic boarding school, where are Pondok Pesantren (Islamic Boarding School) Al-Munawwir Krapyak, Yogyakarta. Al-Munawwir Krapyak is one of the Islamic boarding schools that has a variety of focus programs so that variations of lexicon in Arabic are found. The method used in this study is a combined of research and development theory in the social by Sugiyono (2022), ethnographic method by James P. Spradley (2006), and language research method by Sudaryanto (2015). There are consists of three stages, specifically (1) the stage of data collection which was carried out with active participation observations and unstructure interview, then (2) the stage of data analysis, and (3) the last was the stage of presentation the results of data analysis are presented informally. The results of this research show that the activities carried out by the cottage community are in accordance with the original meaning of the lexicon form itself. In addition, the lexicon in this cottage has been affected by regional languages, causing language fusion (linguistic assimilation) whose changes the form of the language from its original language. ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ø¥ÙŠØ¬Ø§Ø¯ ÙˆÙˆØµÙ Ø®ØµØ§Ø¦Øµ ØªÙ†ÙˆÙŠØ¹Ø§Øª Ø§Ù„Ù…Ø¹Ø¬Ù… Ø§Ù„Ø¹Ø±Ø¨ÙŠ ÙÙŠ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ù‡Ùˆ Ù…Ø¹Ù‡Ø¯ "Ø§Ù„Ù…Ù†ÙˆÙ‘Ø±" Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ø¨ÙƒØ±Ø§Ø¨ÙŠØ§Ùƒ ØŒ Ù…Ù† ÙˆØ¬Ù‡Ø© Ù†Ø¸Ø±ÙŠØ© Ù„ØºÙˆÙŠØ© Ø£Ù†Ø«Ø±ÙˆØ¨ÙˆÙ„ÙˆØ¬ÙŠØ©. ÙŠØ¹Ø¯ Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ù…Ù† Ø§Ù„Ù…Ø¹Ø§Ù‡Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙŠ ÙŠÙˆÙƒÙŠØ§ÙƒØ±ØªØ§ Ø§Ù„ØªÙŠ ØªØØªØ¶Ù† Ù…Ø¬Ù…ÙˆØ¹Ø© Ù…ØªÙ†ÙˆØ¹Ø© Ù…Ù† Ø§Ù„Ø¨Ø±Ø§Ù…Ø¬ Ø§Ù„ØªÙŠ ØªØ±ÙƒØ² Ø¹Ù„Ù‰ Ø°Ù„Ùƒ Ø¨ØÙŠØ« ÙŠØªÙ… Ø§Ù„Ø¹Ø«ÙˆØ± Ø¹Ù„Ù‰ Ø§Ø®ØªÙ„Ø§ÙØ§Øª ÙÙŠ Ø§Ù„Ù…Ø¹Ø¬Ù… Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…ØªØ¨Ø¹Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ø·Ø±ÙŠÙ‚Ø© Ù…Ø´ØªØ±ÙƒØ© Ø¨ÙŠÙ† Ù†Ø¸Ø±ÙŠØ© Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¨ØØ« ÙˆØ§Ù„ØªØ·ÙˆÙŠØ± ÙÙŠ Ø§Ù„Ù…Ø¬Ø§Ù„ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ø³ÙˆØºÙŠÙˆÙ†Ùˆ (2022) ÙˆØ§Ù„ØªÙŠ ÙŠØªÙ… Ø§Ø³ØªÙƒÙ…Ø§Ù„Ù‡Ø§ Ø¨Ø¹Ø¯ Ø°Ù„Ùƒ Ø¨Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¥Ø«Ù†ÙˆØºØ±Ø§ÙÙŠØ© Ø¨ÙˆØ§Ø³Ø·Ø© Ø¬ÙŠÙ…Ø³ Ø³. Ø³Ø¨Ø±Ø§Ø¯Ù„ÙŠ (2006) ÙˆØ·Ø±ÙŠÙ‚ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù„ØºÙˆÙŠ Ø³ÙˆØ¯Ø§Ø±ÙŠØ§Ù†ØªÙˆ (2015).Â Ù‡Ù†Ø§Ùƒ Ø«Ù„Ø§Ø« Ù…Ø±Ø§ØÙ„ Ù„Ù„Ø¨ØØ« ØŒ ÙˆÙ‡ÙŠ Ù…Ø±ØÙ„Ø© Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„ØªÙŠ ØªØªÙ… Ø¹Ù† Ø·Ø±ÙŠÙ‚ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© Ø§Ù„Ù…Ø´Ø§Ø±ÙƒÙŠØ© Ø§Ù„Ù†Ø´Ø·Ø© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø§Øª Ø§Ù„Ù…ÙØªÙˆØØ©ØŒ Ø«Ù… Ù…Ø±ØÙ„Ø© ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§ØªØŒ ÙˆØ§Ù„Ø£Ø®ÙŠØ±Ø© Ù‡ÙŠ Ù…Ø±ØÙ„Ø© Ø¹Ø±Ø¶ Ù†ØªØ§Ø¦Ø¬ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„ØªÙŠ ØªØªÙ… Ø¨Ø´ÙƒÙ„ ØºÙŠØ± Ø±Ø³Ù…ÙŠ. ØªØ¸Ù‡Ø± Ù†ØªØ§Ø¦Ø¬ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† Ø§Ù„Ø£Ù†Ø´Ø·Ø© Ø§Ù„ØªÙŠ ÙŠÙ‚ÙˆÙ… Ø¨Ù‡Ø§ Ø§Ù„Ù†Ø§Ø³ ÙÙŠ Ø§Ù„Ù…Ø¹Ù‡Ø¯ ØªØªÙˆØ§ÙÙ‚ Ù…Ø¹ Ø§Ù„Ù…Ø¹Ù†Ù‰ Ø§Ù„Ø£ØµÙ„ÙŠ Ù„Ø´ÙƒÙ„ Ø§Ù„Ù…Ø¹Ø¬Ù… Ù†ÙØ³Ù‡. Ø¨Ø§Ù„Ø¥Ø¶Ø§ÙØ© Ø¥Ù„Ù‰ Ø°Ù„ÙƒØŒ ØªØ£Ø«Ø± Ø§Ù„Ù…Ø¹Ø¬Ù… ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø¨Ø§Ù„Ù„ØºØ§Øª Ø§Ù„Ù…ØÙ„ÙŠØ© ØŒ Ù…Ù…Ø§ ØªØ³Ø¨Ø¨ ÙÙŠ Ø§Ù†Ø¯Ù…Ø§Ø¬ Ø§Ù„Ù„ØºØ© (Ø§Ù„Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù„ØºÙˆÙŠ) Ø§Ù„Ø°ÙŠ ØªØºÙŠØ± Ø´ÙƒÙ„ Ø§Ù„Ù„ØºØ© Ù…Ù† Ù„ØºØªÙ‡Ø§ Ø§Ù„Ø£ØµÙ„ÙŠØ©.